AI for Fraud Detection and Accounting System Security : Implementation in Indonesian Islamic Banks - Sujana, Deni Amin; Laela, Sugiyarti Fatma (Jurnal Akuntansi dan Bisnis, 2025)
This research study examines the impact of Artificial Intelligence (AI) on enhancing the security of Islamic banking accounting systems in Indonesia. Specifically, it focuses on AI's ability to accurately and efficiently detect fraud. The research used path analysis to investigate how AI's fraud detection capabilities affect accounting system security. The study involved IT professionals, auditors, and risk management staff in Islamic banking as respondents. A detailed questionnaire was developed to measure AI's role, revealing positive and significant effects on accounting system security. These effects were observed both directly and indirectly through fraud detection accuracy and efficiency. Interestingly, the study found that AI has a greater direct impact on security than its mediated effect, indicating that while AI improves fraud detection, its full potential in bolstering accounting system security has yet to be fully realized. The findings offer practical insights for Islamic banks, regulators, and stakeholders to implement and evaluate AI technology for fraud detection.